When a Team is More Like a Group: Improving Individual Motivation by Managing Integrity Through Team Action Processes. (2nd January 2019) - Cady, Steven H.; Brodke, Michelle; Parker, Nurit
Abstract : An important interdisciplinary opportunity to conduct field research examines how to improve an individual's contribution on a team that requires little to no interaction in order to accomplish the team's mission, goals, and objectives. This field study examined 308 volunteers organized into 78 membership recruitment teams. A specific planned team intervention was implemented which blended two approaches: integrity management and team action processes. The results of the intervention showed that even when a team is more like a group, individual effort improves. The intervention had a significant indirect effect on individual performance through individual effort. Results further demonstrate that the intervention is distinct from self-efficacy and team confidence. Identifiability of contributions and visibility of effort are discussed as mechanisms through which team interventions influence effort and performance within teams for which the task itself does not require higher levels of interdependent work.